Surgical treatment of cementoblastoma associated with apicoectomy and endodontic therapy: Case report - Costa, Bernardo Cesar [UNESP]; Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Afonso Miranda Chaves, Maria das Gracas [UNESP]; Costa, Renan Roberto da [UNESP]; Real Gabrielli, Mario Francisco [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Baishideng Publishing Group Inc, 2016)
This case report describes the surgical removal of cementoblastoma associated with apicoectomy and endodontic therapy. The patient, an 18-year-old man, presented pain in the region of the mandibular body on the right side. On clinical exam, bone expansion was observed in the region at the bottom of the vestibular sulcus, pain on palpation, slight extrusion of tooth 46 with presence of pulp vitality. Radiographic exams demonstrated the presence of a radiopaque area and discrete radiolucent halo associated with the root of tooth 46, suggesting the diagnosis of cementoblastoma. Endodontic treatment of tooth 46 was performed and exeresis of the lesion by apicoectomy. Twelve months after the first surgery, recurrence of the lesion was observed, and a new apicoectomy was necessary, this time up to the middle third of the root. Clinical radiographic control 12 mo after the second surgical intervention demonstrated absence of signs and symptoms, radiographic repair, with tooth 46 shown to be fully functional.
Keywords: Endodontic treatment; Cementoblastoma; Apicoectomy